Arabic Manuscripts and Spanish Arabists: The Gayangos Collection at the Royal Academy of History (Madrid) (1st part) - Ait Belaid, Ahmed (Anaquel de Estudios Árabes, 2007)
This paper is about the catalogue of the Gayangos Collection of Arabic manuscripts at the Royal Academy of History. Descriptive cataloging includes the title, name of author, subject matter, date of copy and composition, technical data of the manuscripts and other observations of interest.